MÍDIA E DISCURSO: UM ESTUDO DO DISCURSO DA VEJA SOBRE O FUNK CARIOCA - Zanon, Leonardo Cordeiro (2009)
This paper approaches Veja Magazine, publication of the publishing company Abril, with the objective of identifying which speech is used in articles that approach the funk from Rio de Janeiro as subject. It is a qualitative research, with a descriptive profile, in which the French line theories of Speech Analysis were used as subsidy for analysis. The corpus is composed of a clipping, based on seven news articles of the publication. It was verified that the funk from Rio de Janeiro is related with sexuality and consumerism and the magazine uses an authoritarian speech to impose differences between the social classes of the ones that enjoy it, and the readers of the publication, besides, the magazine looks for denigrate funk s image, giving opinions and using irony.(AU)